Nickel-metal hydride battery, positive electrode material as well as preparation method and application of positive electrode material

By using raw materials such as nickel salts, hydroxycobalt compounds, titanium salts, fluoropolymers and polyamine carboxylic acids in the nickel-hydrogen battery positive electrode materials, combined with specific preparation methods, the problems of poor performance and low energy density of nickel-hydrogen battery at extreme temperatures are solved, and a nickel-hydrogen battery positive electrode material with a wide temperature range, high energy density and excellent stability are achieved.

CN119650605AActive Publication Date: 2025-03-18GUANGDONG XINLI ENERGY CO LTD ZHONGSHAN CITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411623678.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing nickel-hydrogen batteries have poor performance at extreme temperatures, low energy density, limited cycle life and stability, especially when fast charging and discharging and high-rate discharge, they are prone to performance degradation or safety problems.

Method used

A new type of nickel-hydrogen battery positive electrode material is adopted, and its raw materials include component A (nickel salt, hydroxycobalt compound) and component B (titanium salt, fluoropolymer, solvent). A positive electrode material with excellent chemical inertness and corrosion resistance is formed through a specific preparation method, and the high temperature stability of the material is improved by the introduction of component C (polyamine carboxylic acid, halogenated alcohol, alkali, acid chloride).

Benefits of technology

The wide temperature range, high energy density and excellent stability of nickel-hydrogen batteries are achieved, which enhances the battery's power output capability and cycle stability, and reduces the risk of performance degradation at extreme temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134115570000221
    Figure BDA0005134115570000221
Patent Text Reader

Abstract

The invention discloses a nickel-metal hydride battery, a positive electrode material and a preparation method and application thereof. Raw materials of the nickel-metal hydride battery positive electrode material comprise a component A and a component B. The component A comprises nickel salt. A hydroxyl cobalt compound; wherein the component B comprises a titanium salt; a fluorine-containing polymer; and a solvent. The nickel-metal hydride battery provided by the invention has the advantages of wide temperature application range, high energy density and excellent stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nickel-hydrogen batteries, and in particular to a nickel-hydrogen battery, a positive electrode material, and a preparation method and application thereof. Background Art

[0002] Nickel-Metal Hydride (NiMH), as an important type of rechargeable battery, has become a widely used energy storage solution in consumer electronics, power tools, hybrid vehicles and other fields after years of development and improvement.

[0003] Nickel-metal hydride batteries are composed of positive electrodes, negative electrodes, electrolytes and separators, among which the positive electrode material has a crucial impact on its performance. Traditional nickel-metal hydride batteries mainly use nickel hydride as the active material for the positive electrode, and metal hydride as the negative electrode. This design enables nickel-metal hydride batteries to have high energy density and good environmental friendliness to a certain extent. Compared with nickel-cadmium batteries, nickel-metal hydride batteries avoid the use of harmful heavy metal cadmium, have a longer cycle life and higher safety.

[0004] However, existing NiMH batteries still have some technical limitations in some aspects. First, the operating temperature range of NiMH batteries is relatively narrow, especially in extreme temperatures (such as low or high temperatures), which limits their use in some specific applications. Secondly, although NiMH batteries are superior to NiCd batteries in energy density, compared with lithium-ion batteries, NiMH batteries still have lower energy density, which is insufficient in some applications that require high energy density. In addition, the cycle life and stability of NiMH batteries are also limited to a certain extent, especially during rapid charging and discharging and high-rate discharge, which are prone to performance degradation or safety issues.

[0005] These technical challenges are closely related to the cathode materials of nickel-hydrogen batteries. The choice of cathode materials directly affects the energy density, cycle life and stability of the battery. Although the traditional nickel-hydrogen battery cathode material nickel-hydrogen compounds can provide relatively stable electrochemical performance, their stability at high temperatures is poor, which can easily lead to a shortened battery life or performance degradation. In addition, the hydrogen storage capacity and conductivity of nickel-hydrogen compounds also directly affect the power characteristics and cycle life of the battery.

[0006] Based on this, it is urgent to develop a new type of nickel-hydrogen battery positive electrode material to solve the above problems. Summary of the invention

[0007] The object of the present invention is to provide a positive electrode material and a nickel-hydrogen battery, so that the nickel-hydrogen battery has a wide temperature use range, high energy density and excellent stability.

[0008] The first aspect of the present invention is:

[0009] Provided is a nickel-hydrogen battery positive electrode material.

[0010] The second aspect of the present invention is:

[0011] Provided is a method for preparing a positive electrode material for a nickel-hydrogen battery.

[0012] The third aspect of the present invention is:

[0013] Application of the nickel-hydrogen battery positive electrode material.

[0014] The invention also provides a nickel-hydrogen battery.

[0015] Specifically, the technical solution adopted according to the first aspect of the present invention is:

[0016] A nickel-hydrogen battery positive electrode material, the raw materials of the nickel-hydrogen battery positive electrode material include component A and component B:

[0017] Among them, component A includes:

[0018] Nickel salts;

[0019] Hydroxocobalt compounds;

[0020] Among them, component B includes:

[0021] Titanium salts;

[0022] Fluoropolymers;

[0023] Solvent.

[0024] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0025] The raw materials of the positive electrode material of the nickel-hydrogen battery of the present invention include component A and component B, wherein the nickel salt in component A can store and release charges with high efficiency, thereby providing a higher specific capacity, and the hydroxycobalt compound can promote the electrode reaction, increase the reaction rate and efficiency, thereby enhancing the power performance of the battery;

[0026] Among them, the fluorinated polymer in component B has excellent chemical inertness and corrosion resistance, and can protect the positive electrode material from the erosion of the electrolyte, thereby extending the service life of the battery and improving the stability of the battery. However, the fluorinated polymer has a very low surface energy, and part of the fluorinated polymer will cover the surface of the positive electrode material, thereby affecting the contact area between the positive electrode material and the electrolyte, resulting in a decrease in the diffusion rate of ions, a decrease in the discharge and charging rate of the battery, and affecting the power output of the battery;

[0027] In order to compensate for the adverse effects of fluorine-containing polymers, the present invention also introduces titanium salt into component B. Titanium salt has good electrical conductivity and chemical stability, which can compensate for the reduced contact area caused by the low surface energy of polytetrafluoroethylene to a certain extent, and help to improve the electronic and ion conduction efficiency between the positive electrode material and the electrolyte, thereby improving the discharge and charging rates of the battery and enhancing the power output capacity of the battery.

[0028] According to one embodiment of the present invention, the titanium salt comprises titanium dioxide.

[0029] According to one embodiment of the present invention, the titanium dioxide is introduced in situ into the positive electrode material, so that it can compete with the fluorine-containing polymer for adsorption on the surface active sites of the positive electrode material, replacing the position of the fluorine-containing polymer on the surface of the positive electrode material, thereby reducing the thickness and mass of the covering layer formed by the fluorine-containing polymer on the surface of the positive electrode material, thereby greatly avoiding the adverse effects of the fluorine-containing polymer.

[0030] According to one embodiment of the present invention, the raw materials of the nickel-hydrogen battery positive electrode material also include zinc oxide. Zinc oxide can increase the conductivity and electrochemically active surface area of ​​the electrode, thereby improving the energy density and power density of the battery. Cobalt oxide can provide additional reaction active sites during the battery charging and discharging process, which helps to enhance the reaction rate and stability of the electrode.

[0031] According to one embodiment of the present invention, the raw material of the nickel-hydrogen battery positive electrode material includes the following components A and B in parts by weight:

[0032] Wherein, component A comprises the following components in parts by weight:

[0033] Nickel salt, 100-120 parts;

[0034] Hydroxocobalt compound, 20-30 parts;

[0035] Wherein, component B comprises the following components in parts by weight:

[0036] Titanium salt, 10-15 parts;

[0037] Fluoropolymer, 20-25 parts.

[0038] According to one embodiment of the present invention, the hydroxycobalt compound includes at least one of cobalt oxyhydroxide, hydroxycobaltate and hydroxycobalt oxide.

[0039] According to one embodiment of the present invention, the fluorine-containing polymer includes at least one of polytetrafluoroethylene, fluorinated polyethylene, fluorinated polyurethane, fluorinated polyisobutylene and fluorinated polystyrene.

[0040] According to one embodiment of the present invention, the raw material of the positive electrode material of the nickel-hydrogen battery further includes a C component, and the C component includes polyamine carboxylic acid, halogenated alcohol, base, acyl chloride and solvent.

[0041] Since the raw material of the positive electrode material of the nickel-hydrogen battery of the present invention contains a hydroxy cobalt compound, although the hydroxy cobalt compound can enhance the power performance of the battery, the hydroxy cobalt compound is not very stable at high temperatures, such as cobalt oxyhydroxide (CoOOH) will decompose into cobalt oxide (Co3O4) at high temperatures, and this reaction intensifies as the temperature rises, and this decomposition will affect the performance and stability of the positive electrode material of the battery. Therefore, the problem is improved by introducing the C component.

[0042] The C component contains a carboxyl compound, which can form a hydrogen bond between the hydroxyl group and the carboxyl group with the hydroxycobalt compound, thereby stabilizing the structure of the hydroxycobalt compound, reducing the free mobility of the hydroxyl group, and avoiding its decomposition under high temperature conditions. In addition, the C component also contains a chloroacetyl chloride group, which can form a stable chemical bond under high temperature conditions, thereby stabilizing the structure of the positive electrode material. It can react with the oxide on the surface of the material to form a protective surface layer to prevent further oxidation or structural damage.

[0043] According to one embodiment of the present invention, the polyamine carboxylic acid includes at least one of diethylenetriaminepentaacetic acid, ethylenediaminetetraacetic acid and hydroxyethylethylenediaminetriacetic acid.

[0044] According to one embodiment of the present invention, the preparation method of the C component comprises the following steps: mixing polyamine carboxylic acid, base and halogenated alcohol in a solvent, heating and reacting to obtain a mixture, adding acyl chloride to the mixture under a protective atmosphere, and heating and reacting to obtain the C component.

[0045] According to one embodiment of the present invention, the acyl chloride includes at least one of chloroacetyl chloride, benzoyl chloride, acetyl chloride, isovaleryl chloride, valeryl chloride and butyryl chloride.

[0046] Specifically, the technical solution adopted according to the second aspect of the present invention is:

[0047] A method for preparing the positive electrode material of the nickel-hydrogen battery comprises the following steps:

[0048] S1. Mixing nickel salt and hydroxycobalt compound to obtain a first composite material;

[0049] S2: mixing titanium salt and fluorine-containing polymer in a solvent, and heating and reacting the mixture to obtain a first modifier;

[0050] S3: immersing the first composite material into the first modifier, taking it out and drying it, so as to obtain the positive electrode material of the nickel-hydrogen battery.

[0051] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:

[0052] The method for preparing the positive electrode material of a nickel-hydrogen battery of the present invention comprises the following steps: first, a first composite material is formed by mixing a nickel salt and a hydroxycobalt compound, and nickel and cobalt elements are effectively combined to provide a basis for the performance of the subsequent positive electrode material of the battery. Secondly, a titanium salt and a fluorine-containing polymer are mixed in a solvent to obtain a first modifier, which not only helps to adjust the chemical composition and structure of the material, but also improves the electrochemical performance and cycle stability of the material. Finally, the first composite material is immersed in the first modifier, and after drying, the positive electrode material of a nickel-hydrogen battery is obtained. The entire preparation process is simple and efficient, suitable for industrial production needs, and can produce high-quality positive electrode materials on a large scale.

[0053] Another aspect of the present invention further provides a nickel-hydrogen battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the nickel-hydrogen battery positive electrode material as described in the first embodiment. Since the application adopts all the technical solutions of the nickel-hydrogen battery positive electrode material, it at least has all the beneficial effects brought by the technical solutions of the above embodiments.

[0054] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION

[0055] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0056] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the embodiments, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0057] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0058] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0059] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0060] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0061] Example 1

[0062] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0063] Among them, component A includes:

[0064] Nickel salts;

[0065] Hydroxocobalt compounds;

[0066] Among them, component B includes:

[0067] Titanium salts;

[0068] Fluoropolymers;

[0069] Solvents;

[0070] Among them, the C component includes:

[0071] Polyaminocarboxylic acids;

[0072] Halogenated alcohols;

[0073] Alkali;

[0074] Acid chlorides;

[0075] Solvent.

[0076] Wherein, the nickel salt is nickel hydroxide;

[0077] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0078] Wherein, the titanium salt is titanium chloride;

[0079] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0080] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0081] Wherein, the halohydrin is 2-bromoethanol;

[0082] Wherein, the alkali is sodium hydroxide;

[0083] wherein the acyl chloride is chloroacetyl chloride;

[0084] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0085] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0086] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0087] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0088] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0089] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0090] Example 2

[0091] The difference between Example 2 and Example 1 is that the hydroxycobalt compound in Example 2 is potassium hydroxycobaltate.

[0092] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0093] Among them, component A includes:

[0094] Nickel salts;

[0095] Hydroxocobalt compounds;

[0096] Among them, component B includes:

[0097] Titanium salts;

[0098] Fluoropolymers;

[0099] Solvents;

[0100] Among them, the C component includes:

[0101] Polyaminocarboxylic acids;

[0102] Halogenated alcohols;

[0103] Alkali;

[0104] Acid chlorides;

[0105] Solvent.

[0106] Wherein, the nickel salt is nickel hydroxide;

[0107] Wherein, the hydroxycobalt compound is potassium hydroxycobaltate;

[0108] Wherein, the titanium salt is titanium chloride;

[0109] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0110] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0111] Wherein, the halohydrin is 2-bromoethanol;

[0112] Wherein, the alkali is sodium hydroxide;

[0113] wherein the acyl chloride is chloroacetyl chloride;

[0114] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0115] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of potassium hydroxycobaltate and 10 parts of a binder to obtain a first composite material;

[0116] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0117] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0118] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0119] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0120] Example 3

[0121] The difference between Example 3 and Example 1 is that the titanium salt in Example 3 is titanium acetate.

[0122] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0123] Among them, component A includes:

[0124] Nickel salts;

[0125] Hydroxocobalt compounds;

[0126] Among them, component B includes:

[0127] Titanium salts;

[0128] Fluoropolymers;

[0129] Solvents;

[0130] Among them, the C component includes:

[0131] Polyaminocarboxylic acids;

[0132] Halogenated alcohols;

[0133] Alkali;

[0134] Acid chlorides;

[0135] Solvent.

[0136] Wherein, the nickel salt is nickel hydroxide;

[0137] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0138] Wherein, the titanium salt is titanium acetate;

[0139] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0140] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0141] Wherein, the halohydrin is 2-bromoethanol;

[0142] Wherein, the alkali is sodium hydroxide;

[0143] wherein the acyl chloride is chloroacetyl chloride;

[0144] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0145] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0146] S2: titanium acetate and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0147] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0148] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0149] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0150] Example 4

[0151] The difference between Example 4 and Example 1 is that the fluorine-containing polymer in Example 4 is fluorinated polyethylene.

[0152] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0153] Among them, component A includes:

[0154] Nickel salts;

[0155] Hydroxocobalt compounds;

[0156] Among them, component B includes:

[0157] Titanium salts;

[0158] Fluoropolymers;

[0159] Solvents;

[0160] Among them, the C component includes:

[0161] Polyaminocarboxylic acids;

[0162] Halogenated alcohols;

[0163] Alkali;

[0164] Acid chlorides;

[0165] Solvent.

[0166] Wherein, the nickel salt is nickel hydroxide;

[0167] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0168] Wherein, the titanium salt is titanium chloride;

[0169] Wherein, the fluorinated polymer is fluorinated polyethylene;

[0170] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0171] Wherein, the halohydrin is 2-bromoethanol;

[0172] Wherein, the alkali is sodium hydroxide;

[0173] wherein the acyl chloride is chloroacetyl chloride;

[0174] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0175] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0176] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of fluorinated polyethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0177] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0178] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0179] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0180] Example 5

[0181] The difference between Example 5 and Example 1 is that Example 5 does not contain component C.

[0182] A nickel-hydrogen battery positive electrode material, comprising component A and component B:

[0183] Among them, component A includes:

[0184] Nickel salts;

[0185] Hydroxocobalt compounds;

[0186] Among them, component B includes:

[0187] Titanium salts;

[0188] Fluoropolymers;

[0189] Solvent.

[0190] Wherein, the nickel salt is nickel hydroxide;

[0191] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0192] Wherein, the titanium salt is titanium chloride;

[0193] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0194] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0195] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0196] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0197] S3: immersing the first composite material into the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0198] Example 6

[0199] The difference between Example 6 and Example 1 is that the amount of component A is different.

[0200] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0201] Among them, component A includes:

[0202] Nickel salts;

[0203] Hydroxocobalt compounds;

[0204] Among them, component B includes:

[0205] Titanium salts;

[0206] Fluoropolymers;

[0207] Solvents;

[0208] Among them, the C component includes:

[0209] Polyaminocarboxylic acids;

[0210] Halogenated alcohols;

[0211] Alkali;

[0212] Acid chlorides;

[0213] Solvent.

[0214] Wherein, the nickel salt is nickel hydroxide;

[0215] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0216] Wherein, the titanium salt is titanium chloride;

[0217] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0218] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0219] Wherein, the halohydrin is 2-bromoethanol;

[0220] Wherein, the alkali is sodium hydroxide;

[0221] wherein the acyl chloride is chloroacetyl chloride;

[0222] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0223] S1: mixing 100 parts of nickel hydroxide, 20 parts of zinc oxide, 25 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0224] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0225] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0226] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0227] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0228] Example 7

[0229] The difference between Example 7 and Example 1 is that the amount of component B is different.

[0230] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0231] Among them, component A includes:

[0232] Nickel salts;

[0233] Hydroxocobalt compounds;

[0234] Among them, component B includes:

[0235] Titanium salts;

[0236] Fluoropolymers;

[0237] Solvents;

[0238] Among them, the C component includes:

[0239] Polyaminocarboxylic acids;

[0240] Halogenated alcohols;

[0241] Alkali;

[0242] Acid chlorides;

[0243] Solvent.

[0244] Wherein, the nickel salt is nickel hydroxide;

[0245] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0246] Wherein, the titanium salt is titanium chloride;

[0247] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0248] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0249] Wherein, the halohydrin is 2-bromoethanol;

[0250] Wherein, the alkali is sodium hydroxide;

[0251] wherein the acyl chloride is chloroacetyl chloride;

[0252] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0253] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0254] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.08 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 15 parts of polytetrafluoroethylene and 90 parts of tetrafluoroethane are added to obtain a first modifier;

[0255] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0256] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0257] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0258] Example 8

[0259] The difference between Example 8 and Example 1 is that the amount of component C is different.

[0260] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0261] Among them, component A includes:

[0262] Nickel salts;

[0263] Hydroxocobalt compounds;

[0264] Among them, component B includes:

[0265] Titanium salts;

[0266] Fluoropolymers;

[0267] Solvents;

[0268] Among them, the C component includes:

[0269] Polyaminocarboxylic acids;

[0270] Halogenated alcohols;

[0271] Alkali;

[0272] Acid chlorides;

[0273] Solvent.

[0274] Wherein, the nickel salt is nickel hydroxide;

[0275] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0276] Wherein, the titanium salt is titanium chloride;

[0277] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0278] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0279] Wherein, the halohydrin is 2-bromoethanol;

[0280] Wherein, the alkali is sodium hydroxide;

[0281] wherein the acyl chloride is chloroacetyl chloride;

[0282] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0283] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0284] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0285] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0286] S4: add 28 parts of diethylenetriaminepentaacetic acid, 25 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 13 parts of dimethyl sulfoxide and 40 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 15 parts of chloroacetyl chloride and 9 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0287] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0288] Comparative Example 1

[0289] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not contain component B.

[0290] A nickel-hydrogen battery positive electrode material, comprising component A and component C:

[0291] Among them, component A includes:

[0292] Nickel salts;

[0293] Hydroxocobalt compounds;

[0294] Among them, the C component includes:

[0295] Polyaminocarboxylic acids;

[0296] Halogenated alcohols;

[0297] Alkali;

[0298] Acid chlorides;

[0299] Solvent.

[0300] Wherein, the nickel salt is nickel hydroxide;

[0301] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0302] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0303] Wherein, the halohydrin is 2-bromoethanol;

[0304] Wherein, the alkali is sodium hydroxide;

[0305] wherein the acyl chloride is chloroacetyl chloride;

[0306] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0307] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0308] S2: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0309] S3: mixing the first composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0310] Comparative Example 2

[0311] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, titanium dioxide is not generated by in-situ hydrothermal method, but titanium dioxide is directly added in step S2.

[0312] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0313] Among them, component A includes:

[0314] Nickel salts;

[0315] Hydroxocobalt compounds;

[0316] Among them, component B includes:

[0317] Titanium dioxide;

[0318] Fluoropolymers;

[0319] Solvents;

[0320] Among them, the C component includes:

[0321] Polyaminocarboxylic acids;

[0322] Halogenated alcohols;

[0323] Alkali;

[0324] Acid chlorides;

[0325] Solvent.

[0326] Wherein, the nickel salt is nickel hydroxide;

[0327] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0328] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0329] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0330] Wherein, the halohydrin is 2-bromoethanol;

[0331] Wherein, the alkali is sodium hydroxide;

[0332] wherein the acyl chloride is chloroacetyl chloride;

[0333] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0334] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0335] S2 mixes titanium dioxide, anhydrous ethanol, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane to obtain a first modifier;

[0336] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0337] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, heat to 65°C, stir to react for 10 hours, extract to obtain a mixture, add 21 parts of chloroacetyl chloride and 12 parts of acetone to the mixture under a protective atmosphere, heat to 60°C, stir to react for 6 hours, extract to obtain a second modifier;

[0338] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0339] Comparative Example 3

[0340] The difference between Comparative Example 3 and Example 1 is that in step S4 of Comparative Example 3, chloroacetyl chloride is not added.

[0341] A nickel-hydrogen battery positive electrode material, comprising component A, component B and component C:

[0342] Among them, component A includes:

[0343] Nickel salts;

[0344] Hydroxocobalt compounds;

[0345] Among them, component B includes:

[0346] Titanium salts;

[0347] Fluoropolymers;

[0348] Solvents;

[0349] Among them, the C component includes:

[0350] Polyaminocarboxylic acids;

[0351] Halogenated alcohols;

[0352] Alkali;

[0353] Solvent.

[0354] Wherein, the nickel salt is nickel hydroxide;

[0355] Wherein, the hydroxycobalt compound is cobalt oxyhydroxide;

[0356] Wherein, the titanium salt is titanium chloride;

[0357] Wherein, the fluorine-containing polymer is polytetrafluoroethylene;

[0358] Wherein, the polyamine carboxylic acid is diethylenetriaminepentaacetic acid;

[0359] Wherein, the halohydrin is 2-bromoethanol;

[0360] Wherein, the alkali is sodium hydroxide;

[0361] A method for preparing a positive electrode material for a nickel-hydrogen battery comprises the following steps:

[0362] S1: mixing 100 parts of nickel hydroxide, 15 parts of zinc oxide, 20 parts of cobalt oxyhydroxide and 10 parts of a binder to obtain a first composite material;

[0363] S2: titanium chloride and anhydrous ethanol are mixed to obtain a sol with a titanium ion concentration of 0.1 M. While stirring, sodium hydroxide is slowly added to the sol, the pH value is adjusted to 8.0, and the reaction is carried out at 150° C. for 6 hours. After cooling, 20 parts of polytetrafluoroethylene and 100 parts of tetrafluoroethane are added to obtain a first modifier;

[0364] S3: immersing the first composite material in the first modifier, taking it out and drying it after 2 hours, and heat treating it at 500° C. for 2 hours to obtain a second composite material;

[0365] S4: add 28 parts of diethylenetriaminepentaacetic acid, 23 parts of 2-bromoethanol and 2 parts of sodium hydroxide to 11 parts of dimethyl sulfoxide and 35 parts of acetonitrile, raise the temperature to 65°C, stir and react for 10 hours, extract and obtain a second modifier;

[0366] S5: mixing the second composite material and the second modifier in acetonitrile in a weight ratio of 3:1, and removing the solvent after 24 hours to obtain a positive electrode material for a nickel-hydrogen battery.

[0367] Performance Test:

[0368] The hydrogen battery positive electrode material prepared in Examples 1-6 and Comparative Examples 1-3 was coated on the surface of nickel foam, pressed and dried to prepare a positive electrode. A saturated calomel electrode was used as a reference electrode, a platinum sheet electrode was used as a counter electrode, and 6 mol / L KOH was used as an electrolyte to prepare a nickel-hydrogen battery. The electrochemical performance was tested using a battery test system and an electrochemical workstation, and a three-electrode system. The test results are shown in Table 1.

[0369] Among them, the cycle test method is as follows:

[0370] The battery prepared above was placed at 60° C. to test its cycle performance. The cycle steps were to repeatedly charge and discharge the lithium-ion battery, and calculate the cycle capacity retention rate of the lithium-ion battery. When the capacity retention rate of the lithium-ion battery was less than 80%, the cycle test was terminated and the number of cycles was recorded.

[0371] Table 1

[0372]

[0373]

[0374] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A positive electrode material for a nickel-hydrogen battery, characterized in that: The raw materials of the nickel-hydrogen battery positive electrode material include component A and component B: Among them, component A includes: Nickel salts; Hydroxocobalt compounds; Among them, component B includes: Titanium salts; Fluoropolymers; Solvent.

2. A nickel-hydrogen battery positive electrode material according to claim 1, characterized in that: The raw materials of the nickel-hydrogen battery positive electrode material include the following components A and B in parts by weight: Wherein, component A comprises the following components in parts by weight: Nickel salt, 100-120 parts; Hydroxyl cobalt compound, 20-30 parts; Wherein, component B comprises the following components in parts by weight: Titanium salt, 10-15 parts; Fluoropolymer, 20-25 parts.

3. The positive electrode material for a nickel-hydrogen battery according to claim 1, characterized in that: The cobalt hydroxy compound includes at least one of cobalt oxyhydroxide, hydroxycobaltate and cobalt hydroxy oxide.

4. The positive electrode material for a nickel-hydrogen battery according to claim 1, characterized in that: The fluorine-containing polymer includes at least one of polytetrafluoroethylene, fluorinated polyethylene, fluorinated polyurethane, fluorinated polyisobutylene and fluorinated polystyrene.

5. The positive electrode material for a nickel-hydrogen battery according to claim 1, characterized in that: The raw materials of the positive electrode material of the nickel-hydrogen battery also include a C component, which includes polyamine carboxylic acid, halogenated alcohol, alkali, acyl chloride and solvent.

6. A nickel-hydrogen battery positive electrode material according to claim 5, characterized in that: The polyamine carboxylic acid includes at least one of diethylenetriaminepentaacetic acid, ethylenediaminetetraacetic acid and hydroxyethylethylenediaminetriacetic acid.

7. The positive electrode material for a nickel-hydrogen battery according to claim 5, characterized in that: The preparation method of the C component comprises the following steps: mixing polyamine carboxylic acid, base and halogenated alcohol in a solvent, heating and reacting to obtain a mixture, adding acyl chloride to the mixture under a protective atmosphere, and heating and reacting to obtain the C component.

8. The positive electrode material for a nickel-hydrogen battery according to claim 5, characterized in that: The acyl chloride includes at least one of chloroacetyl chloride, benzoyl chloride, acetyl chloride, isovaleryl chloride, valeryl chloride and butyryl chloride.

9. A method for preparing a positive electrode material for a nickel-hydrogen battery as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mixing nickel salt and hydroxycobalt compound to obtain a first composite material; S2: mixing titanium salt and fluorine-containing polymer in a solvent, and heating and reacting the mixture to obtain a first modifier; S3: immersing the first composite material into the first modifier, taking it out and drying it, so as to obtain the positive electrode material of the nickel-hydrogen battery.

10. A nickel-hydrogen battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a nickel-hydrogen battery positive electrode material as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of hydroxy cobaltous oxide-coated nickel hydroxide composite material for alkaline secondary battery

    CN108123125A

  • Preparation method of multilayer alpha-nickel hydroxide composite material for alkaline secondary batteries

    CN109935799A

  • Nickel-metal hydride battery and preparation method thereof

    CN116404274A

  • Nickel metal hydride battery design

    CN1985389A

  • Nickel hydrogen secondary battery and positive electrode thereof

    JP1998074512A